(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the modern era, globalization has dramatically transformed communication processes across the globe, making intercultural communication essential for individuals and organizations navigating an increasingly interconnected world. Theories of intercultural communication, such as Edward T. Hall’s distinction between high-context and low-context communication, Geert Hofstede’s cultural dimensions theory, and Stella Ting-Toomey’s Face-Negotiation Theory, offer critical frameworks for understanding the dynamics of cross-cultural interactions. Meanwhile, the development of global communication is influenced by technological advancements and the spread of digital media, which have reshaped how cultures exchange information and ideas. This paper explores key theories of intercultural and global communication, providing insights into the challenges and opportunities that arise from communicating across diverse cultural contexts. It also discusses the impact of digital globalization, the implications of cultural imperialism, and the hybridization of cultural practices, offering a comprehensive overview of communication in the globalized world. The article concludes by emphasizing the need for cultural sensitivity, inclusivity, and adaptive communication strategies to foster effective intercultural interactions in a rapidly evolving global environment.